Dysbaric osteonecrosis screening in submarine escape instructors - (:unkn) unknown (AEROSPACE MEDICAL ASSOC, 2004)
Introduction: Dysbaric osteonecrosis (DON) is an avascular bone necrosis that can be seen in divers and compressed air workers. Submarine escape instructors constitute a specific group who are exposed to hyperbaric conditions with a constant profile. Methods: We screened 21 Turkish Navy submarine escape instructors and evaluated 147 skeletal radiographs for dysbaric osteonecrosis. Two instructors who had suspicious DON lesions on the X-rays underwent examination by MRI of the suspected sites. Results: We found no evidence of DON in the radiographs and MRIs of the submarine escape instructors. Discussion: We concluded that the risk of DON is very low for submarine escape instructors who work at the Submarine Escape Training Tower (SETT) at a depth of 60 ft and who strictly obey the decompression rules.
Keywords: dysbaric; osteonecrosis; submarine; escape; decompression; BONE NECROSIS; DIVERS